Learning lessons from the economic crisis in self-employment - Bernard Njindan Iyke; Sin-yu Ho (Contemporary Economics, 2020)
The main objective of this article is to test the hypothesis that the economic crisis has resulted in significant changes in the socioeconomic and labor profile of the new self-employed in Spain between 2008 and 2013. Additionally, it is intended to determine if there are homogeneous profiles of new self-employed workers that allow to set clusters, and, if so, to check how these clusters have changed in the studied period. To verify the above-mentioned hypotheses, it has been carried out a descriptive analysis followed by a Cluster Analysis, using the Continuous Sample of Working Lives data. The research concludes that the economic recession has been accompanied by a fall in the number of new self-employed between 2008 and 2013, along with a significant change in their socio-demographic and occupational profile. There is also evidence of the existence of several clusters of self-employed, with heterogeneous sociodemographic and labor characteristics. The composition and features of these clusters evolved in parallel to the economic situation, showing an intense increase in the educational level and a reduction in the job stability between 2008 and 2013.
Keywords: E32; J21; M13; 330; entrepreneurship; self-employment; economic crisis; Business cycle; self-employed workers profiles